Survei Kebugaran Jasmani Siswa SDN 164/I Sridadi Fase C - Parman, Agus; Trinando, Jeffry; Fitromel, Decky; Lubis, Herudi; Siregar, Muhammad Suhron; Widowati, Atri (MAN Insan Cendekia Jambi, 2025)
The purpose of this study was to determine how strong the students of SDN 164/I Sridadi Phase C are in terms of physical fitness. Physical fitness is very important to help children learn and develop physically. This study used a quantitative descriptive survey. Phase C students at SDN 164/I Sridadi were selected purposively for the research sample, with a series of Indonesian Student Fitness Tests phase C. With the results of the Child Ball Test, 4 students were classified as Very Good with a presentation of 29%, 6 students were classified as Good with a percentage of 43%, 2 students were classified as Moderate with a percentage of 14%, and 2 students were classified as less with a percentage of 14%, the Tok-Tok Ball Test obtained 5 students classified as Very Good with a presentation of 36%, 7 students were classified as Good with a percentage of 50%, and 2 students were classified as Moderate with a percentage of 14%. The Move The Ball Test obtained 5 students classified as Very Good with a percentage of 14%, 7 students classified as Good with a percentage of 50%, and 2 students classified as Moderate with a percentage of 36%. The Shuttle Run 8 x 10m Test obtained, 10 students classified as Good with a percentage of 71%, and 4 students classified as Moderate with a percentage of 29%. The 600m Run Test obtained, 2 students classified as Very Good with a percentage of 14%, and 12 students classified as Good with a percentage of 86%. Based on the results of the study conducted, students in grades 5 and 6 of SDN 164/I Sridadi, Muara Bulian District, Batanghari Regency, have a good level of physical fitness.